2019
DOI: 10.29185/hayuretim.556669
|View full text |Cite
|
Sign up to set email alerts
|

Yalova’da Yetiştirilen Kıvırcık Kuzularında Büyüme-Gelişme ve Bazı Morfolojik Özelliklerinin Belirlenmesi

Abstract: Sonuç: Araştırmanın yapıldığı bölgede yetiştirilen Kıvırcık ırkı koyunların çeşitli dönem canlı ağırlık ortalamalarının yeterli düzeye çıkarılabilmesi için öncelikli olarak yetiştirici koşullarının iyileştirilmesi gerektiği ortaya çıkmıştır. Ayrıca yapağı dağılımındaki farklılık ve az oluşu, kuyruk yapısının da diğer Kıvırcıklardan daha kısa olduğu gözlemlenmiştir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Environmental factors are known to cause some morphological differences even within the same breed. Some studies are suggesting that Kıvırcık sheep in Yalova is a subtype/variety of Kıvırcık breed (Kaymakçı, 2010;Alarslan and Aygün, 2019a;Alarslan and Aygün, 2019b). However, with the genetic diversity analysis, it was revealed that the Yalova genotype was genetically separated from Kıvırcık, Tahirova and Eşme sheep (Anonymous, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental factors are known to cause some morphological differences even within the same breed. Some studies are suggesting that Kıvırcık sheep in Yalova is a subtype/variety of Kıvırcık breed (Kaymakçı, 2010;Alarslan and Aygün, 2019a;Alarslan and Aygün, 2019b). However, with the genetic diversity analysis, it was revealed that the Yalova genotype was genetically separated from Kıvırcık, Tahirova and Eşme sheep (Anonymous, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The nose is convex. Yalova genotype has a lower distribution of fleece on the dorsal and dorsolateral, bare chest and abdomen, a short tail with low fleece or no naked tail (Alarslan and Aygün, 2019a;Alarslan and Aygün, 2019b).…”
Section: Introductionmentioning
confidence: 99%